Arabic Language Learning Management at an Integrated Islamic Elementary Schools in Sokoharjo/ إدارة تعليم اللغة العربية في المدارس الابتدائية الإسلامية المتكاملة في سوكوهارجو - Rio Kurniawan (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2022)
This research departs from the phenomenon of Integrated Islamic Schools (SIT) where the researchers took a sample of 5 Integrated Islamic Elementary Schools (SDIT) as a sample of the diversity of Integrated Islamic Schools in Sukoharjo. The study took SDIT because Arabic is a lesson in every SDIT, so there is a need for management in learning Arabic to achieve the objectives of learning Arabic at SDIT. This research is a descriptive qualitative research, with data collection techniques of observation, interviews, and documentation. By analyzing data using data reduction, data delivery, and conclusions. In the discussion to achieve Arabic learning objectives that have been planned by an institution, the need for Arabic learning management which includes Arabic learning planning, organizing Arabic learning, implementation of Arabic learning, evaluation of Arabic learning. So each SDIT to achieve the objectives of learning Arabic, it is necessary to manage Arabic learning by being able to develop according to their respective characteristics and still maintain the characteristics so that learning management is in accordance with the objectives of each foundation or educational institution so that learning Arabic can be effective and efficient